Conductive graphite fiber as a stable host for zinc metal anodes. (1st August 2017) - Wang, Li-Ping; Li, Nian-Wu; Wang, Tai-Shan; Yin, Ya-Xia; Guo, Yu-Guo; Wang, Chun-Ru
Highlights: Using graphite fiber as a skeleton for zinc metal anodes in hybrid aqueous batteries. After 350 cycles at 1C, a relatively low voltage hysteresis (below 50 mV) of Zn@GF has been achieved. The growth of dendritic Zn has been significantly retarded. Abstract: Zn metal with high theoretical capacity (820 mA h g −1 ), environmental-friendly properties and low cost is very competitive to be as an anode for aqueous batteries. However, uncontrollable growth of dendritic zinc in these batteries during plating/stripping process of zinc ions not only leads to a low Coulombic efficiency but also brings safety hazards, which have obstructed the application of secondary Zn-based batteries. Here we use high conductive carbon fiber-graphite felt (GF) as collector and electrodeposit zinc under constant voltage to fabricate a self-supported Zn@GF negative electrode. The graphite felt provides this anode larger electroactive area to transport electrons faster and loads zinc in a more event way, thus preluding the zinc plating in several specific directions. This composite anode offers an efficient solution to get a dendrite-free cycling behavior of zinc-based batteries and might be promising in advanced aqueous batteries for large-scale energy storage.